(untitled) (Letras, 2025)
This paper offers a comparative view of fin-de-siècle poetry in the French- and Spanish-speaking Caribbean islands, addressing common and unique characteristics according to literary heritage and transcultural dynamics arising from the transplantation of European literature and art into different historical and cultural contexts that shaped Haitian and Cuban poetry. As a result of this process, two fin-de-siècle literary movements emerged: modernism in the Spanish-American sphere and the Génération de la Ronde in Haiti. Poems by two great representatives of these movements, Julián del Casal (1863-1893) and Edmond Laforest (1876- 1915), will be discussed in light of Homi Bhabha’s theory of cultural translation and hibridity.